Cultural concepts of distress among Albanian young adults living in Switzerland - a qualitative study - Pnishi, Imer; Shala, Mirëlinda; Morina, Naser; Maercker, Andreas; Heim, Eva (Frontiers in Psychology, 2024)
Objectives Existing research recognizes the critical role that social, sociodemographic, and acculturative processes play in increasing vulnerability for experiencing psychological distress among second-generation migrants. However, to date, far too little attention has been given to the study of psychological distress in this social group. The main objective of this study is to examine cultural identities, as well as expressions and causes of psychological distress among second-generation Albanian-speaking migrants in Switzerland. Methods Semi-structured qualitative interviews were conducted with 13 Albanian-speaking participants between 19 and 35 years of age using the interview of the Barts Explanatory Model Inventory. Data were analyzed by qualitative content analysis using MAXQDA-2018 software. Findings Study participants showed bicultural identities, which caused value conflicts and a feeling of being “caught” between Swiss and Albanian culture. Some participants experienced the fear of disappointing their parents. Others find it difficult to deal with conflicting norms and values. Parentification was another important cause within their cultural concept of distress. At the same time, (implicit) social support, i.e., spending time with the family and the community, was an important coping mechanism. Conclusion Second-generation immigrants are exposed to specific risk factors for psychological distress. A better understanding of these risk factors and their coping mechanisms is essential for providing them with meaningful support services, both in prevention and psychotherapy.